EFFECTS OF DIFFERENT TYPES OF PHYSICAL EXERCISE ON SLEEP QUALITY OF DIFFERENT INDIVIDUALS: A LITERATURE REVIEW - Maciej Hutkowski; Patrycja Markowicz; Anna Skrzypek; Zuzanna Chwostek; Krzysztof Biłyk; Mikołaj Zbrożek; Paulina Biedroń; Bartłomiej Kosiarski; Hanna Maruchniak; Wiktoria Marzec (International Journal of Innovative Technologies in Social Science, 2026)
Research objectives: Sleep disturbances, including insomnia, are unfortunately a common occurrence among adults, negatively impacting various aspects of their physical and mental health. Available pharmacotherapy is restricted by adverse effects and limited safety of long-term usage. Consequently, interest in non-pharmacological approach including physical exercise intervention has increased. This work aims to review research published since 2018 on the topic of effects of physical exercise on sleep quality in adults. Methods: PubMed, ResearchGate, MDPI, and Google Scholar were searched for RCTs, reviews, systematic reviews or meta-analyses in English, published between 2018 and 2025. Studies on children, with small populations or lacking interventions were excluded. Key findings: Regular physical exercise, particularly aerobic exercise or resistance training, improved subjective sleep quality and reduced insomnia severity, among its other positive effects. Physical exercise of moderate intensity, with the duration of 30-60 minutes, conducted 3-5 times a week for 8-12 weeks proved to be most effective in the context of improving sleep quality. Moreover, some of other types of physical exercise were more beneficial for specific populations and resulted in additional health benefits. Conclusions: Current evidence supports regular physical exercise as safe, easily accessible, and effective intervention for improving sleep quality in adult population. Future research should focus on broader utilization of objective methods of sleep quality measures, standardizing exercise protocol for the best effect, further exploration of indirect pathways of interaction between sleep quality and physical activity, effects of different combinations of approaches in treating insomnia, and long-term follow up of the interventions.